Mind–body interventions: Applications in neurology - Wahbeh, Helané (2008)
OBJECTIVE: Half of the adults in the United States use complementary and alternative medicine with mind–body therapy being the most commonly used form. Neurology patients often turn to their physicians for insight into the effectiveness of the therapies and resources to integrate them into their care. The objective of this article is to give a clinical overview of mind–body interventions and their applications in neurology. METHODS: Medline and PsychInfo were searched on mind–body therapies and neurologic disease search terms for clinical trials and reviews and published evidence was graded. RESULTS: Meditation, relaxation, and breathing techniques, yoga, tai chi, and qigong, hypnosis, and biofeedback are described. Mind–body therapy application to general pain, back and neck pain, carpal tunnel syndrome, headaches, fibromyalgia, multiple sclerosis, epilepsy, muscular dysfunction, stroke, aging, Parkinson disease, stroke, and attention deficit–hyperactivity disorder are reviewed. CONCLUSIONS: There are several conditions where the evidence for mind–body therapies is quite strong such as migraine headache. Mind–body therapies for other neurology applications have limited evidence due mostly to small clinical trials and inadequate control groups.